Retaining Walls in theory and in practice a text-book for students - Coleman, T. E. (E. & F.N. Spon, 1914)
The essential principles which govern a sound knowledge of retaining walls are explained in detail, whilst at the same time the use of complicated formula and advanced mathematics have been avoided as much as possible.
Includes index.
Keywords: Retaining walls.; elektronické knihy; electronic books